2016
DOI: 10.1038/srep18781
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Ricin Toxin by Nanosecond Pulsed Electric Fields Including Evidences from Cell and Animal Toxicity

Abstract: Ricin is one of the most toxic and easily produced plant protein toxin extracted from the castor oil plant, and it has been classified as a chemical warfare agent. Here, nanosecond pulsed electric fields (nsPEFs) at 30 kV/cm (pulse durations: 10 ns, 100 ns, and 300 ns) were applied to inactivating ricin up to 4.2 μg/mL. To investigate the efficacy, cells and mice were tested against the ricin treated by the nsPEFs via direct intraperitoneal injection and inhalation exposure. Results showed that nsPEFs treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…The field-induced change in the fluorescence lifetime of NADH is considered to arise from the physical effect: Intermolecular interactions of NADH with surrounding amino acids of protein may be changed by the application of electric fields, as an irreversible process. In fact, the change in protein structure was reported to be induced by nsPEF using ricin, that is, the secondary structure of ricin was slightly changed by nsPEF, resulting in the reduction of the toxicity of ricin. We have previously shown that the fluorescence lifetime of NADH has a tendency to increase with decreasing polar environment around NADH, and the increase in the lifetime with binding to a protein can also be explained in terms of the decrease in the hydrophilicity of NADH .…”
Section: Discussionmentioning
confidence: 99%
“…The field-induced change in the fluorescence lifetime of NADH is considered to arise from the physical effect: Intermolecular interactions of NADH with surrounding amino acids of protein may be changed by the application of electric fields, as an irreversible process. In fact, the change in protein structure was reported to be induced by nsPEF using ricin, that is, the secondary structure of ricin was slightly changed by nsPEF, resulting in the reduction of the toxicity of ricin. We have previously shown that the fluorescence lifetime of NADH has a tendency to increase with decreasing polar environment around NADH, and the increase in the lifetime with binding to a protein can also be explained in terms of the decrease in the hydrophilicity of NADH .…”
Section: Discussionmentioning
confidence: 99%
“…The electric-field effect on the dynamics and function of biological systems may depend on the cell membrane capacitance and on the pulse duration of the applied field, which enables selective applications of pulsed electric field in specific organelles and specific living cells. 21 23 If a pulse shorter than the charging time of the outer membrane is applied to living systems, the pulsed electric field may induce changes in subcellular organelles, signal proteins, and biochemical processes, without affecting the outer plasma membrane and organelles. For example, apoptosis is induced by the application of nsPEF, with a pulse width of 10–50 ns and a field strength of 40 or 45 kV cm –1 in HeLa cells.…”
Section: Introductionmentioning
confidence: 99%
“…The electric-field effect on the dynamics and function of biological systems may depend on the cell membrane capacitance and on the pulse duration of the applied field, which enables selective applications of pulsed electric field in specific organelles and specific living cells. If a pulse shorter than the charging time of the outer membrane is applied to living systems, the pulsed electric field may induce changes in subcellular organelles, signal proteins, and biochemical processes, without affecting the outer plasma membrane and organelles. For example, apoptosis is induced by the application of nsPEF, with a pulse width of 10–50 ns and a field strength of 40 or 45 kV cm –1 in HeLa cells. , In the present study, on the basis of the pulse-height dependence and pulse-width dependence of the field-induced change in the fluorescence lifetime, it is shown that apoptosis of cancer cells induced by application of pulsed electric fields is considerably more effective than that of normal cells, suggesting that ultrashort pulsed electric field is applicable for cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The ricin and endotoxin suspensions were prepared by vigorously vortexing 40 μg of ricin or 50 ng endotoxin per mL deionized water for 20 min at a vortex rate of 3200 rpm (Vortex Genie-2, Scientific Industries Co., Ltd.). Detailed information about ricin preparation and exposure can also be found in another work . Here, ozone was generated by an ozone generator (Guangzhou Environmental Protection Electric Co., Ltd., China) using a corona discharge method.…”
Section: Methodsmentioning
confidence: 48%
“…Detailed information about ricin preparation and exposure can also be found in another work. 39 Here, ozone was generated by an ozone generator (Guangzhou Environmental Protection Electric Co., Ltd., China) using a corona discharge method. The ozone was further diluted with indoor air for rat exposure experiments, and the ozone concentration in the exposure chamber was approximately 5 ppm.…”
Section: Methodsmentioning
confidence: 99%